Prosumption as a Result of Changes in Consumer Behavior with the Example of Food Industry - Bednarz, Joanna (Studia Oeconomica Posnaniensia, 2026)
Contemporary consumption is characterized by contradictory trends of consumerism and sustainable consumption, as well as the increasingly raising inclination towards prosumption. More and more consumers cease to be passive, uncritical, and open towards goods and services offered by entrepreneurs, imitating existing lifestyles. Contrary to this, they are sovereign, aware, active, creative, commonly manifesting their individuality and by such behaviour expressing themselves among other people. This trend was noticed by food manufacturers, who progressively engage their clients in the process of creating the offer. The most involved prosumers are invited to create new products, packaging or invent marketing slogans. Customers who are less active participate in actions organized by the producers, evaluate and comment on products online on forums and e-shops. The article has a theoretical and empirical character. The aim of this paper is to show the changes in consumer behaviour with the example of the food industry with a particular emphasis on the trend of prosumption.